2022
DOI: 10.3389/fonc.2022.830910
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Risk System Based on Shear Wave Elastography and BI-RADS Categories in Assessing Axillary Lymph Node Metastasis of Invasive Breast Cancer—A Multicenter Study

Abstract: PurposeTo develop a risk stratification system that can predict axillary lymph node (LN) metastasis in invasive breast cancer based on the combination of shear wave elastography (SWE) and conventional ultrasound.Materials and MethodsA total of 619 participants pathologically diagnosed with invasive breast cancer underwent breast ultrasound examinations were recruited from a multicenter of 17 hospitals in China from August 2016 to August 2017. Conventional ultrasound and SWE features were compared between posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…The most signi cant advantage of VTIQ is its objectivity, which eliminates the subjectivity of operators, and provides high reproducibility of tests [35]. Previous research has revealed that the E max of positive ALN was higher than that of negative ALN, and E min was lower [14,21]. The results in the training cohort were consistent with these ndings.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The most signi cant advantage of VTIQ is its objectivity, which eliminates the subjectivity of operators, and provides high reproducibility of tests [35]. Previous research has revealed that the E max of positive ALN was higher than that of negative ALN, and E min was lower [14,21]. The results in the training cohort were consistent with these ndings.…”
Section: Discussionsupporting
confidence: 76%
“…VTIQ is a novel technique based on shear wave velocity (SWV) from different tissues, which can provide quantitative information for tumor heterogeneity [12,13]. It shows good e cacy for assessing ALN status, with an accuracy of 0.632 reported by Zhang et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…As far as the overall study was concerned, there was no definite evidence to indicate which was better, SE or SWE ( 18 ). However, the role of SWE in the diagnosis, differentiation, efficacy evaluation and prediction of breast cancer was obvious ( 13 , 14 , 27 ). One study demonstrated the superior predictive value of Emax in combination with BI-RADS category 4a in breast cancer screening ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two main modes of elastography have become established in clinical practice: strain elastography (SE) and shear wave elastography (SWE) (12). SE and SWE have shown significant value in previous studies (13)(14)(15)(16). SWE could provide useful diagnostic information for tissue stiffness to improve the accuracy of B-ultrasound diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed the use of ultrasound elastography in the examination of many organs, such as lymph nodes, liver, and thyroid ( 15 , 16 ). Shear wave elastography (SWE), a novel elastography technique, provides quantitative information on measuring tissue stiffness ( 17 , 18 ). Recently, SWE was reported to be associated with the axillary lymph node metastasis in breast cancer ( 19 ).…”
Section: Introductionmentioning
confidence: 99%